Clinical Features of Patients Undergoing the Head-Up Tilt Test and Its Safety and Efficacy in Diagnosing Vasovagal Syncope in 4,873 Patients - Xu, Lingping; Cao, Xiangqi; Wang, Rui; Duan, Yichao; Yang, Ye; Hou, Junlong; Wang, Jing; Chen, Bin; Xue, Xianjun; Zhang, Bo; Ma, Hua; Sun, Chaofeng; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The head-up tilt test (HUTT) is a useful diagnostic tool in patients with suspected vasovagal syncope (VVS). Objectives: We aimed to investigate the direct drug-potentiated HUTT in patients with recurrent syncope or precursor syncope and to assess the diagnostic value of the direct drug-potentiated HUTT. Methods: The medical history and direct drug-potentiated HUTT records of patients who complained of syncope or precursor syncope and who visited The Xianyang Central Hospital from January 2016 to December 2020 were retrospectively reviewed. Results: A total of 4,873 patients (age = 43.8 ± 17.6 years; male = 2,064 [42.4%]) were enrolled in our study. Overall, 2,343 (48.1%) showed positive responses as follows: 1,260 (25.9%) with the mixed type, 34 (0.7%) with the cardioinhibitory type, 580 (11.9%) with the vasodepressor type, 179 (3.7%) with postural tachycardia syndrome (POTS), and 290 (6.0%) with orthostatic hypotension (OH). The study showed that prior to syncope or near-syncope symptoms, patients first presented an increase in heart rate (HR), followed by decreases in blood pressure (BP) and HR successively. Among the patients in the syncope group, the sensitivity of the HUTT was 65.9%, which was significantly higher than a sensitivity of 44.8% for patients in the non-syncope group (P < 0.01). The sensitivity of the HUTT was higher for females than males in both the syncope group (52.6% in males and 77.9% in females, P < 0.01) and the non-syncope group (36.5% in males and 50.6% in females, P < 0.01). Within the four age groups (<20, 21–40, 41–60, and >60 years old), the sensitivities were 74.7%, 67.7%, 45.6%, and 31.2%, respectively. And all gender, age and symptom (whether suffered from a syncope or not) significantly affected the positive responses of HUTT. There were two adverse events and no deaths during the HUTT in this study. Conclusion: The direct drug-potentiated HUTT is a safe and highly sensitive tool with which to diagnose VVS. Patients with precursor syncope symptoms without syncope should undergo a HUTT, especially young females presenting with weakness and sweating, which can decrease the probability of a misdiagnosis or a missed diagnosis.